Contractor’s Attitude towards Risk and Risk Management in Construction in Two Western Provinces of Vietnam - Phan, V. T. (Engineering, Technology & Applied Science Research, 2020)
Risk management is an important task in construction management that helps the contractor to actively identify, evaluate, control, and minimize negative impacts of risks on the project, thereby ensuring its effectiveness. People involved in the construction industry need to be well - equipped with information and knowledge to manage risks adequately and systematically. The purpose of this research is to explore the attitude towards risk and risk management in construction projects of the Vietnamese construction industry, with emphasis on the perspective of contractors. The research data are collected through a questionnaire associated with in-depth semi-structured interviews. The results indicate that the perception of risk within the Vietnamese construction industry includes both threats and opportunities. The majority of professionals in the industry have a risk-neutral approach, contrary to previous research. The importance of implementing effective risk management is shared, in the planning and production phase while risk identification was perceived to be the most important out of the four core processes.